The Other Wes Moore Guide for Resident Assistants - Kansas State University, K-State First (Kansas State University. K-State First., 2015)
Developed for resident assistants, this guide to "The Other Wes Moore" by Wes Moore includes a short timeline, chapter excerpts, and discussion questions.
Keywords: Community building; First-year experience program; Common reading program; Guide; The Other Wes Moore; Residence Life; Brochures